(untitled) (Research, Society and Development, 2021)
Nutritional status is a factor of clinical relevance in the health of the elderly. The aim of the study was to develop accessible food supplements for the elderly, as well as an instrument for nutritional counseling. This is an experimental study, in which food supplements and dietary preparations fortified with them were developed. The preparations were made considering the current nutritional recommendations for supplementation in the elderly, and were tested in a hospital kitchen. The nutritional composition of the supplements was calculated from the technical data sheets, with the aid of a nutritional software. The average cost was calculated based on the market values ​​from August to October 2020. Five supplements (basic preparations) were developed, as well as six recipes in which they could be incorporated. The supplements achieved caloric and protein recommendations for supplementation for the elderly, and along with the fortified recipes, they were suitable for diabetes, dysphagia and lactose intolerance. A booklet for nutritional counseling was prepared. Homemade options for food supplements can be affordable alternatives for elderly people at nutritional risk.